Disclosure of accountability practices on websites of Malaysian city councils / Dayang Hafiza Abang Ahmad, Corina Joseph and Roshima Said - Abang Ahmad, Dayang Hafiza; Joseph, Corina; Said, Roshima (Universiti Teknologi MARA, 2021)
Accountability in the public sector has been widely scrutinised due to the increasing demand from various stakeholders including the public. Disclosure practices could substantially improve the accountability of the public sector through the usage of technology, i.e., websites. This paper examined the extent of the disclosure of accountability practices (DACP) on the websites of the entire Malaysian city councils. A content analysis was carried out to analyse the content of official websites of 14 city council. A Modified Accountability Disclosure Index (MOADI) comprised of 100 disclosure items was adopted to measure the extent of the DACP of Malaysian city councils. There was an average of 59% of the extent of DACP found on the website of city councils. The findings further indicated that the highest and the least frequent information disclosed by the city councils were classified under delivery and other information, respectively. This paper contributes a significant finding which highlights the importance of the website as a medium for discharging accountability to enhance the overall administrative system in local authorities'. The findings provide valuable insights and implications about accountability practices to several groups of stakeholders including the local authorities, regulators, and the community.